Bifunctional Europium for Operando Catalyst Thermometry in an Exothermic Chemical Reaction. Issue 52 (24th November 2022) - Terlingen, Bas J. P.; Arens, Tjom; van Swieten, Thomas P.; Rabouw, Freddy T.; Prins, P. Tim; de Beer, Michiel M.; Meijerink, Andries; Ahr, Mathieu P.; Hutter, Eline M.; van Lare, Coert E. J.; Weckhuysen, Bert M.
Abstract: Often the reactor or the reaction medium temperature is reported in the field of heterogeneous catalysis, even though it could vary significantly from the reactive catalyst temperature. The influence of the catalyst temperature on the catalytic performance and vice versa is therefore not always accurately known. We here apply EuOCl as both solid catalyst and thermometer, allowing for operando temperature determination. The interplay between reaction conditions and the catalyst temperature dynamics is studied. A maximum temperature difference between the catalyst and oven of +16 °C was observed due to the exothermicity of the methane oxychlorination reaction. Heat dissipation by radiation appears dominating compared to convection in this set‐up, explaining the observed uniform catalyst bed temperature. Application of operando catalyst thermometry could provide a deeper mechanistic understanding of catalyst performances and allow for safer process operation in chemical industries. Abstract : Temperature determines the reaction kinetics, thermodynamics and catalyst stability. However, very limited information is known about the local catalyst temperature. Here, operando thermometry over bifunctional Eu 3+ is performed to study the interplay between reaction conditions and the catalyst temperature dynamics in the exothermic methane oxychlorination reaction.